1985
DOI: 10.1002/ajim.4700080412
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of epidermal carcinogenesis by repeated damage to mouse skin

Abstract: Chemically induced epidermal carcinogenesis is usually divided into two stages: initiation, which involves the conversion of some epidermal cells into latent neoplastic cells; and promotion, which results in tumors. The hallmark of chemical promoters is epidermal hyperplasia. The hyperplasia caused by a strong promoter, such as 12-O-tetradecanoylphorbol-13-acetate (TPA), differs morphologically from that caused by weak promoters, such as acetic acid and mezerin. The epidermal regeneration that follows abrasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In line with this scenario we found that TPA treatment can stimulate migration of Lgr5+ progeny to the IFE. TPA treatment induces a strong inflammatory and hyperproliferative response in mouse skin and is typically used for epidermal tumor promotion, and TPA has been shown to be as effective as deep skin wounding in promoting papilloma formation in mice (36). Although treatment with TPA can provide the important signals responsible for the migration of the potential tumor initiating cells, the key signals for HF cell migration into the wound are as of yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this scenario we found that TPA treatment can stimulate migration of Lgr5+ progeny to the IFE. TPA treatment induces a strong inflammatory and hyperproliferative response in mouse skin and is typically used for epidermal tumor promotion, and TPA has been shown to be as effective as deep skin wounding in promoting papilloma formation in mice (36). Although treatment with TPA can provide the important signals responsible for the migration of the potential tumor initiating cells, the key signals for HF cell migration into the wound are as of yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogen LRCs may indeed be initiated cells, not necessarily because they retain carcinogen, but because they are stem cells affected before commitment to terminal differentiation (Lajtha, 1979;Buick & Poliak, 1984). Although the long-term presence of the adduct might possibly represent an enduring potential for the formation of initiated cells (Randerath et al 1983) in the murine skin system, the similar tumour responses at one week and one year after initiation (Boutwell, 1964-Roe et al 1972Stenback et al 1981;Van Duuren et al 1975;Loehrkeeta l. 1983;Hennings & Boutwell, 1970;Argyris, 1985a) suggest that the initiated state is established quickly and then maintained.…”
Section: The Significance Of Carcinogen Label-retaining Cells In Two-mentioning
confidence: 99%
“…The consequences of tumour initiation are essentially irreversible and not expressed in the absence of promotion. The tumour responses are evoked whether promotion is begun one week or one year after the exposure to the carcinogen (Boutwell, 1964;Roe et al 1972;Stenbach et al 1981;Van Duuren et al 1975;Loehrke et al 1983;Hennings & Boutwell, 1970;Argyris, 1985a) and are surprisingly similar for a tissue such as the epidermis which is characterized by continuous turnover and cyclic growth and regression of the hair follicles (Hennings & Yuspa, 1985;Argyris, 1963;Potten, 1983;Iversen et al 1968;Leblond, 1964). Conceivably, any epidermal cell could become and remain initiated.…”
Section: The Significance Of Carcinogen Label-retaining Cells In Two-mentioning
confidence: 99%
“…Argyris (24) suggests a follicular origin for papillomas and carcinomas, based on a model of epidermal abrasion that was found to be a tumor-promoting stimulus. The Argyris abrasion protocol entails removing the interfollicular epidermis but leaves the hair follicles undisturbed.…”
Section: Kcfcs In Two-stage Carcinogenesismentioning
confidence: 99%